A way forward for anxiolytic drug development: Testing candidate anxiolytics with anxiety-potentiated startle in healthy humans. (December 2020) - Grillon, Christian; Ernst, Monique
Highlights: There is a need to improve the drug screening process for anxiolytics. Human anxiety models should be used as a screening tool to help select candidate anxiolytics before launching clinical trials. Anxiety-potentiated startle fulfill several key validity criteria as an experimental model of anxiety in humans. Anxiety-potentiated startle is a promising tool for anxiolytic drug development. Abstract: This review introduces a research strategy that may radically transform the pursuit of new anxiolytics, via the use of human models of anxiety in healthy individuals. Despite enormous investments in developing novel pharmacological treatments for anxiety disorders, pharmacotherapy for these conditions remains suboptimal. Most candidate anxiolytics from animal studies fail in clinical trials. We propose an additional screening step to help select candidate anxiolytics before launching clinical trials. This intermediate step moves the evidence for the potential anxiolytic property of candidate drugs from animals to humans, using experimental models of anxiety in healthy individuals. Anxiety-potentiated startle is a robust translational model of anxiety. The review of its face, construct, and predictive validity as well as its psychometric properties in humans establishes it as a promising tool for anxiolytic drug development. In conclusion, human models of anxiety may stir a faster, more efficient path for the development of clinically effective anxiolytics.